2020
DOI: 10.7498/aps.69.20200062
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis of mode coupling and liner energy deposition properties of helicon and Trivelpiece-Gould waves in helicon plasma

Abstract: Based on the finite temperature plasma dielectric tensor model which contains the particle thermal effect, by numerically solving the eigenmode dispersion relation of electromagnetic waves propagating in radially uniform and magnetized warm plasma column which is surrounded by conducting boundary, the mode coupling characteristic and liner damping mechanism induced wave power deposition properties of helicon and Trivelpiece-Gould (TG) waves are parametrically analyzed. The detailed investigations show as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Equations ( 1) and ( 2) can be converted by Fourier change into the following six equations to solve the various components in cold plasma [24][25][26] :…”
Section: Theoretical Formulamentioning
confidence: 99%
“…Equations ( 1) and ( 2) can be converted by Fourier change into the following six equations to solve the various components in cold plasma [24][25][26] :…”
Section: Theoretical Formulamentioning
confidence: 99%
“…HELIC code is composed of Maxwell's equations for a radially non-uniform plasma with the standard cold-plasma dielectric elements S, D, P (= ε xx , iε xy , ε zz ). These equations can be manipulated to give the following set of coupled differential equations for the Fourier transformed variables: [19][20][21]…”
Section: Theoretical Formulamentioning
confidence: 99%
“…( 1)-( 4) are programmed to solve, and four basic functions are generated, namely b r , b z , e r , and e z . In the cylindrical coordinate system, if the plasma is uniform, the basis function b 1,2;z (r) is the Bessel function J m (T 1,2 r), where [21] ST 4 1…”
Section: Theoretical Formulamentioning
confidence: 99%
“…It is worth noting that the electron density is basically the same when the mode converts, even at different input currents. The discharge mode first converts when the density is about 2×10 16 m −3 and it converts for the second time when the density is about (2-3)×10 18 m −3 . If the background magnetic field of the helicon discharge remains constant, the plasma density at the MCS remains unchanged.…”
Section: Discharges At Different Input Currentsmentioning
confidence: 99%
“…There are two wave branches in the solution of the helicon dispersion relation [11]: one is the helicon wave and the other is called the Trivelpiece-Gould wave (TG wave) [12]. Research showed that the power absorption can be more appropriately explained by the strong damping of the TG wave [13][14][15][16]. Another unique phenomenon in helicon discharges is that the plasma density jumps at a certain power, accompanied by a change of discharge mode [17,18].…”
Section: Introductionmentioning
confidence: 99%